Application of mercapto ordered carbohydrate-derived porous carbons for trace detection of cadmium and copper ions in agricultural products. (15th April 2015) - Behbahani, Mohammad; Abolhasani, Jafar; Amini, Mostafa M.; Sadeghi, Omid; Omidi, Fariborz; Bagheri, Akbar; Salarian, Mani
Highlights: Synthesis a novel nanoporous carbon material. High adsorption capacity for Cd and Cu ions. Low detection limit. High thermal and mechanical stability of a novel sorbent. Environment friendly nanoporous material. Abstract: In this paper, we have introduced nanoporous carbon modified with mercapto groups as a new solid-phase method for extraction of cadmium(II) and copper(II) ions. The modified nanoporous carbon sorbent was characterised by thermogravimetric analysis, differential thermal analysis, transmission electron microscopy, Fourier transform infrared spectrometry, X-ray diffraction, and nitrogen adsorption surface area (BET) measurements. Effects of pH value, flow rates, type, concentration and volume of the eluent, breakthrough volume, and effect of other ions were studied. The experimental results show that simultaneous trace cadmium(II) and copper(II) ions can be quantitatively preconcentrated at pH 6.0 with recoveries >97%. Under optimised conditions, limits of detection are 0.04 and 0.09 ng mL −1 for the ions of cadmium and copper respectively, and the precision of the method for analysis of cadmium and copper ions (5.0 μg of each target ions, N  = 8) are 2.4% and 2.1%, respectively. The obtained capacities of mercapto-nanoporous carbon were found to be 145 and 95 mg g −1 for cadmium and copper ions, respectively. The accuracy of the proposed procedure was verified by analysing standard reference material. Finally, the introduced sorbent was successfully applied for trace determination of cadmium and copper ions in food samples.